Statistical Evaluation of Comorbidities and Environmental Factors in COVID-19 Outcomes: Risk Measures and Predictive Analysis Using Odds and Hazard Ratios - Khan, Mohd Rashid; Danish, Faizan; Ahmed Araibi, Mustafa Ibrahim; Elbatal, I.; Almetwally, Ehab M.; Gemeay, Ahmed M.; Triveni, G.R.V.; Jan, Rafia; Reddy, V.R.K.; Rather, Aafaq A. (International Journal of Statistics in Medical Research, 2025)
In this study, we have reviewed studies that highlight the effects of common conditions like heart disease, high blood pressure, congestive heart failure, kidney problems, and emphysema, which offer the largest risk of death caused by COVID-19. Also, explored how physical activity can influence one's resistance to COVID-19, the effects of stat in medications on mortality rates, and the effectiveness of vaccines in reducing fatalities offer valuable avenues for tailored interventions and treatment strategies and the examination of the relationship between exposure to air contamination and the severity of COVID-19 highlights the task of environmental factors in shaping the outcomes of the illness. Primarily, we focused on how comorbidities affect COVID-19 patients and the associations between comorbidities, lifestyle factors, environmental influences, and COVID-19 outcomes, guiding healthcare strategies and future research, and refining responses to the ongoing pandemic. In this study, analysis of COVID-19 studies centered on compiling risk assessments, including 95% confidence intervals along with odds and hazard ratios. The analysis's goal was to gather and assess the different risk metrics provided in this study.